Impact of Rurality, Broiler Operations, and Community Socioeconomic Factors on the Risk of Campylobacteriosis in Maryland. - Zappe Pasturel, Barbara; Cruz-Cano, Raul; Rosenberg Goldstein, Rachel E.; Palmer, Amanda; Blythe, David; Ryan, Patricia; Hogan, Brenna; Jung, Carrianne; Joseph, Sam W.; Min Qi Wang; Mei-Ling Ting Lee; Puett, Robin; et al. (American Journal of Public Health, 2013)
Objectives. We evaluated the combined impact of community-level environmental and socioeconomic factors on the risk of campylobacteriosis. Methods. We obtained Campylobacter case data (2002-2010; n = 3694) from the Maryland Foodborne Diseases Active Surveillance Network. We obtained community-level socioeconomic and environmental data from the 2000 US Census and the 2007 US Census of Agriculture. We linked data by zip code. We derived incidence rate ratios by Poisson regressions. We mapped a subset of zip code-level characteristics. Results. In zip codes that were 100% rural, incidence rate ratios (IRRs) of campylobacteriosis were 6 times (IRR = 6.18; 95% confidence interval [CI] = 3.19, 11.97) greater than those in urban zip codes. In zip codes with broiler chicken operations, incidence rates were 1.45 times greater than those in zip codes without broilers (IRR = 1.45; 95% CI = 1.34, 1.58). We also observed higher rates in zip codes whose populations were predominantly White and had high median incomes. Conclusions. The community and environment in which one lives may significantly influence the risk of campylobacteriosis.